PENGARUH KUALITAS PRODUK, HARGA PRODUK DAN DISTRIBUSI TERHADAP KEPUASAN PELANGGAN SERTA PENGARUHNYA TERHADAP LOYALITAS CUSTOMER (Study Pada PT Berri Indosari) - Alafityanto, A; Djumarno, D (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This research was conducted with the aim to analyze the effect of product quality, product prices and distribution to customer satisfaction and customer loyalty in PT. Berri Indosari. The sample used in this study are taken from 140 respondents taken by simple random sampling technique. Analysis of the data in this study using Structural Equation Modeling (SEM) is done with the help of SmartPLS program version 3. The results showed that the quality of products, product pricing and distribution has positives and significant impact on customer satisfaction in the PT. Berri Indosari. In addition to product quality, product prices and customer satisfaction has positives and significant impact on customer loyalty in PT. Berri Indosari. However, the distribution has no significant effect on customer loyalty in PT. Berri Indosari